2018
DOI: 10.1590/1806-9282.64.01.11
|View full text |Cite
|
Sign up to set email alerts
|

Microcephaly caused by congenital Zika virus infection and viral detection in maternal urine during pregnancy

Abstract: Currently Latin America is undergoing a major epidemic of Zika virus, which is transmitted by Aedes mosquitoes. Concern for Zika virus infection has been increasing as it is suspected of causing brain defects in newborns such as microcephaly and, more recently, potential neurological and autoimmune complications including Guillian-Barré syndrome and acute disseminated encephalomyelitis. We describe a case of virus infection in a 25-year-old woman during the first trimester of her pregnancy, confirmed by labora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 8 publications
1
7
0
Order By: Relevance
“…The main sign observed in these pregnant women was rash and the most common symptoms were myalgia, headache and pruritus. On the other hand, fever was not a frequent symptom, revealing a similar profile to national 9 and international studies 10 .…”
supporting
confidence: 71%
“…The main sign observed in these pregnant women was rash and the most common symptoms were myalgia, headache and pruritus. On the other hand, fever was not a frequent symptom, revealing a similar profile to national 9 and international studies 10 .…”
supporting
confidence: 71%
“…Traveller/non-traveller populations: In this update, we found further evidence that congenital abnormalities occurred in infants born to women travellers returning from ZIKV-affected areas and women remaining in those areas. In total, 25 publications report on 272 congenital abnormalities due to ZIKV infection in travellers 27, 29, 30, 32, 34, 36, 38, 42, 45, 56, 58, 61, 89, 94, 98, 109, 117, 122, 123, 137, 140, 151, 153, 166, 173 , with 109 publications reporting congenital abnormalities due to ZIKV in 2652 non travellers 2426, 28, 31, 33, 35, 37, 3941, 43, 44, 4648, 50, 51, 54, 57, 60, 6279, 81, 8385, 87, 88, 9093, 95– 97, 100, 101, 104– 106, 110113, 115, 116, 118, 119, 121, 124135, 142147, 149, 152, 154, 156164, 167, 168, 171, 172, 175180, 182, …”
Section: Resultsmentioning
confidence: 99%
“…Most clinical studies have demonstrated that high level of ZIKV viral loads can be detected in the urine samples of both adult and infant patients (7, 8). Previous studies show that ZIKV can infect glomerular parenchymal cells and renal proximal tubular epithelial cells, which may serve as potential reservoirs for ZIKV in kidney (9, 10).…”
Section: Introductionmentioning
confidence: 99%